Application Design "Test Job Application" On Android OS Using The AHP Algorithm - Suharjono; Hari Sugiarto; Istiqomah Sumadikarta; Muhammad Ryansyah; Muhammad Hilman Fakhriza; Arman Syah Putra (International Journal of Educational Research & Social Sciences, 2021)
The background of this research is how to make an application that makes it easier for job seekers to find work with an Android-based application method so that it can be done anywhere and anytime with a very small quota. Helped and employers and companies will also be helped. The method used in this research is to use the method of studying literature or literature by reading many journals related to this research, after that make a prototype so that it can be given an appearance. This research will be able to see whether it is successfully used or not. The problem raised in this research is how to help job seekers find work without leaving the house and being able to search for jobs around the world using only an Android based application that can be done from home. This research produces a prototype system that will be made in the future, so that it can help workers in finding work and companies in finding workers.